2022
DOI: 10.3390/agriculture12070994
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulant Effects of Waste Derived Biobased Products in the Cultivation of Ornamental and Food Plants

Abstract: Soluble bio-based substances (SBS) may be isolated from the anaerobic digestate of the organic humid fraction of urban waste; from the whole vegetable compost made from gardening residues and from the compost obtained after aerobic digestion of a mixture of urban waste digestate, gardening residues and sewage sludge. These SBS can be used as sustainable and efficient plant biostimulants in alternatives to the commercial products based on fossil sources such as the Leonardite. The present review summarizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…Several studies evaluated the biostimulant effect of BPs on a wide range of crops 5 , but BPs for lettuce cultivation had never been tested. In lettuce at the shoot level, the treatments BPs150 + MF100% (+ 24% respect to MF100%) and BPs150 + MF60% (+ 22% respect to MF100%) determined a relevant increase of the FW of the edible portion, in accordance with the biostimulant effects observed for other species 10 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluated the biostimulant effect of BPs on a wide range of crops 5 , but BPs for lettuce cultivation had never been tested. In lettuce at the shoot level, the treatments BPs150 + MF100% (+ 24% respect to MF100%) and BPs150 + MF60% (+ 22% respect to MF100%) determined a relevant increase of the FW of the edible portion, in accordance with the biostimulant effects observed for other species 10 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the performance of BPs in agriculture as plant growth biostimulants and antifungal agents had been reported 5 . The BPs, applied to the soil at 50–150 kg/ha, were demonstrated to be more sustainable and efficient plant biostimulants, in comparison to commercial mineral and organo-mineral products (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The advantageous factor of the accumulation of various forms of microbes employed as plant biofertilizers may hinge upon their potentiality under unfavorable conditions of the environments. Studies have revealed the activity of biostimulants when different materials were added together, describing synergistic interactions (Montoneri et al, 2022;Navarro-Leoń et al, 2022;Canellas et al, 2023). This review portrays how biostimulants (microbial-based) can be produced employing the following methods: AMF/PGPR multispecies consortia, a single PGPM strain, and aggregation of PGPMs with inorganic and organic chemicals.…”
Section: Synergistic Response Of Microbial Biostimulant Componentsmentioning
confidence: 99%
“…In this context, municipal biowaste (MBW) is potentially the most sustainable renewable feedstock. It is readily available in every urban settlement in the world and is a negative cost feedstock, since its collection costs are already paid off by citizens' taxes [2][3][4]. Under these circumstances, turning a MBW treatment plant into a biorefinery producing biofuel and biobased value added chemical specialities is an attracting perspective.…”
Section: Introductionmentioning
confidence: 99%